Avaliação de diretrizes de abandono de poços terrestres no Brasil e análise comparativa de custos para o Estado do RN - Costa Filho, Luiz Antônio da (2023)
Oil has been used as an energy source for about 150 years. It Starting to be explored in the Middle East and North America, simpler wells compared to the current ones. In Brazil, oil exploration began many years later, at the end of the 19th century, but it was only in the 1940s that economically viable oil was found. In Rio Grande do Norte, production began in the 1970s, and many of these wells are still in operation today. The useful life of a well is approximately 25 years, and in the last phase it is permanently abandoned. For the correct abandonment of wells, the National Agency of Petroleum, Natural Gas and Biofuels (ANP) launched in 2016 the Well Management and Integrity System (WMIS) through Resolution Nº 46/2016. that established the Barrier Solidarity Set (BSS) as the main element for the abandonment of wells, as well as the IBP, in 2017, published as “Guidelines for Abandonment of Wells” which determined the use of good practices for carrying out the abandonment of wells. Others were published to act in conjunction with the SGIP, such as ANP Resolution No. 699 of 2017 and ANP No. 817 of 2020. The present work aims to survey the regulations and guidelines for the abandonment and razing of onshore wells and a comparative evaluation between the data presented in the ANP's Decommissioning Panel and the estimated calculation carried out by Braga (2021).